THE EFFECT OF NITROGEN FERTILIZATION OF MAIZE ON PROTEIN CONCENTRATION AND IN VITRO FEMENTABILITY OF GRAIN - D BABNIK; J SUŠIN; J VERBIČ (Journal of Central European Agriculture, 2002)
The effect of nitrogen fertilization of maize on fermentability of maize grain in the rumen was studied by means of in vitro method based on the measurement of gas produced during the incubation of samples with rumen liquor. Gas production was recorded continuously up to 72 h incubation time and cumulative gas production was described by the Gompertz equation Y=A*exp(-exp(-d*(t-tm))). Seven treatments, one of them unfertilized and others fertilized with 100 to 250 kg N ha–1, were compared. Grain yield and concentration of crude protein (CP) in grain increased linearly with nitrogen fertilization. Grain yield increased for 25 kg dry matter (DM) ha–1 and CP concentration for 0.13 g kg–1 DM per each additional kg of N. Concentration of CP in grain, which varied from 83 to 115 g kg–1 DM, was closely related to the dynamics of gas production. The maximal gas production rate (MPR) was negatively related to CP concentration in the grain (R2 = 0.53; p < 0.10) and the time of MPR (tm) was positively related to the amount of added N (R2 = 0.74; p < 0.05) and concentration of CP in the grain (R2 = 0.88; p < 0.01). It is likely that intensive N fertilization of maize limits ruminal digestion of maize starch. Due to the shift of starch digestion from the rumen to lower gastrointestinal tract better utilization of energy can be expected in maize grain of extensively fertilized maize than in the grain of maize, in which supply of N is sub-optimal.